Benang Bintik: Eksplorasi Etnomatematika Dilihat Dari Unsur Bangun Datar pada Kain Khas Dayak Kalimantan Tengah - Rahmawati, Laila; Nyoto, Nyoto; Pinardi, Janu (FKIP Universitas Palangka Raya, 2024)
The relationship between students' prior knowledge and real knowledge in their environment can be a consideration in learning. Understanding this real context is related to the standards of the mathematics learning process, namely integration with culture, integration of culture with mathematics learning is called ethnomathematics. Ethnomathematics refers to the learning process that combines mathematical concepts with local cultural wisdom. The purpose of this study is on the Benang Bintik motif of the typical Dayak cloth of Central Kalimantan which contains mathematical elements in it. The type of research conducted is exploratory research with an ethnographic approach, where research seeks causes or things that influence the occurrence of something or is used when researchers do not know exactly and specifically about the object of research. Ethnography is a type of qualitative research, where researchers conduct studies on group culture in natural conditions through observation, interviews and documentation. The results of the exploration carried out found geometric concepts in flat shapes in the form of squares, rectangles, triangles, pentagons, isosceles trapezoids, parallelograms, rhombuses and kites. The concept of this flat shape pattern can be a reference for teaching materials in classroom learning. The use of typical regional cloth motifs will certainly make learning more interesting in mathematics learning. The concept of flat geometry that is usually taught conventionally can be changed contextually through an ethnomathematics approach. Not only does it change the learning paradigm, it can also be a place to preserve local culture, especially the typical Dayak cloth motifs in Central Kalimantan.